Development of fluorescent lateral flow immunoassay for SARS-CoV-2-specific IgM and IgG based on aggregation-induced emission carbon dots - Ju, Jian; Zhang, Xinyu; Li, Lin; Regmi, Sagar; Yang, Guoqiang; Tang, Shixing (Frontiers in Bioengineering and Biotechnology, 2022)
Understanding the dynamic changes in antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is essential for evaluating the effectiveness of the vaccine and the stage for the recovery of the COVID-19 disease. A rapid and accurate method for the detection of SARS-CoV-2-specific antibodies is still urgently needed. Here, we developed a novel fluorescent lateral flow immunoassay (LFIA) platform for the detection of SARS-CoV-2-specific IgM and IgG by the Aggregation-Induced Emission carbon dots binding with SARS-CoV-2 Spike Protein (SSP). The AIE carbon dots (AIE-CDs) is one of the best prospect fluorescent probe materials for exhibiting a high emission efficiency in both aggregate and solid states. The AIE-CDs were synthesized and displayed dual fluorescence emission, which provides a new perspective for the design of high sensitivity testing system. In this work, the novel LFIA platform adopted the AIE carbon dots which are used to detect SARS-CoV-2-specific IgM and IgG conveniently. Furthermore, this sensor had a low LOD of 100 pg/mL. Therefore, these newly developed strategy has potential applications in the areas of public health for the advancement of clinical research.